2016
DOI: 10.1111/asj.12695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary tryptophan : lysine ratios and sanitary conditions on growth performance, plasma urea nitrogen, serum haptoglobin and ileal histomorphology of weaned pigs

Abstract: A total of 180 mixed-sex pigs (Duroc × (Yorkshire × Landrace); average initial body weight of 7.36 ± 0.2 kg) weaned at 21 ± 1 days were fed corn-soybean meal-wheat-based diets to determine the optimal standardized ileal digestible (SID) tryptophan to lysine ratio (Trp : Lys) in a 2 × 5 factorial arrangement (two sanitary conditions: clean (CL) and unclean (UCL), and five dietary treatments (SID Trp : Lys (16, 18, 20, 22 and 24%)). In each sanitary condition, blood was collected on days 0 and 14 to determine pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…Furthermore, the sanitary status related health status may negatively affect the growth response of the animal to nutrient intake. This may be due to gut morphology changes and body metabolic changes measurable as plasma urea nitrogen content (6). Sanitary conditions not only affect performance, but also modify the behavior of animals (7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sanitary status related health status may negatively affect the growth response of the animal to nutrient intake. This may be due to gut morphology changes and body metabolic changes measurable as plasma urea nitrogen content (6). Sanitary conditions not only affect performance, but also modify the behavior of animals (7).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the optimal standardized ileal digestible threonine:lysine for weaned pigs raised under unclean sanitary conditions was higher (66.5% vs. 65%) than for those raised under clean sanitary conditions ( Jayaraman et al., 2015 ). In a growth study, Jayaraman et al. (2016) demonstrated that a room with unclean sanitary conditions had higher NH 3 (26.65 vs. 18.17 ppm) and H 2 S (0.099 vs. 0.010 ppm) compared to the room with clean sanitary conditions.…”
Section: Effects Of Sanitation On Performance and Gut Healthmentioning
confidence: 99%
“…The term gut health in animals is not well-defined, however, numerous indices, such as those relate to gut structure and function, and microbial population, incidences of diarrhea have been used to describe gut health outcomes ( Lalle's et al., 2007 ). The factors that affect gut health and growth performance in piglet husbandry practices include feeding strategies ( Dong and Pluske, 2007 ), exposure to crowding stress ( Khafipour et al., 2014 ), sanitation ( Jayaraman et al., 2016 ; Kahindi et al., 2014 ) and disease conditions ( Opapeju et al., 2009 ). To minimize the adverse effects of weaning and their subsequent consequences, appropriate husbandry management strategies need to be taken to maximize post-weaning performance.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the haptoglobin concentration in the blood of pigs from these eight comparable studies (Fig 6.1), haptoglobin concentration was greater for LSC pigs compared with HSC pigs in four out of six studies that measured this parameter. Jayaraman et al (2016) found a tendency for higher haptoglobin concentration for LSC compared with HSC pigs. The haptoglobin values for Jayaraman et al (2016) were in a higher range than in the other studies.…”
Section: Variation In Conditions For Different Experimental Modelsmentioning
confidence: 84%
“…In literature several studies have been described that used a similar chronic low-grade immune system stimulation model Lee et al, 2005;Jayaraman et al, 2016). Each study uses a combination of factors to create a contrast in immune system stimulation and was compared with the studies described in Chapter 2 and 4 (Table 6.2).…”
Section: Variation In Conditions For Different Experimental Modelsmentioning
confidence: 99%